PENGARUH FAKTOR PSIKOLOGI KONSUMEN TERHADAP KEPUTUSAN MEMINJAM PADA UPK PNPM MANDIRI PERKOTAAN KOTA MATARAM - Erlita Nathalia Lerrick (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
The spearhead of PNPM Mandiri Perkotaan (National Program Of CommunityEmpowwrment-Urban Project) in economic field is the Financial Management Unit which istrusted to distribute the venture capital to expecially the poor people. However, there havebeen many indications that what is faced by the Financial Management Unit (FMU) of theNational Program of Community Empowerment (NPCE) is related to either the people habitor thought which may become the psychological factors for the community in proposing foraloan. This research is aimed at knowing the effect of such psychological factors asmotivation, perception , the teaching, personality, and attitude on the the decision making topropose a loan to FMU_NPCE Urban Project in Mataram. This research is conducted bythe FMU-NPCE Urban Project Mataram in six subdistricts of Mataram, Ampenan,Cakranegara, Selaparang, Sandubaya, and Sekarbela. This research is an associativeresearch related to 100 respondents of Self-help Communiy Group. The respondents areselected through cluster-sampling. The data are collected through questionnaire and thenanalyzed with multiple regression analysis (MRA) using SPSS program. The researchshowed that motivation, perception, the teaching, personality, and the attitude prositivelyand significantly affect the decision. This research also showed that motivation dominantlyaffect the decision to propose a loan to FMU-NPCE Urban Project in Mataram.Keywords :Motivation, Perception, The teaching, Personality, and decision to have loan.